CLASSIFICATION OF PROFESSIONAL EDUCATIONAL PROGRAMS IN THE RUSSIAN FEDERAITION: PROBLEMS AND POSSIBLE DECISIONS - B. A. Sazonov (Высшее образование в России, 2017)
The article considers the principal development stages of classification of professional educational programs in the Russian Federation, the peculiarities of an actual status and possible perspectives of their development. The liberalization of the State educational standards, the expansion of educational institutions independence in relation to the questions of educational programs formation justify the necessity of the development of a new classification system for Russian education. The classification system, which is currently under elaboration, should become a common tool for all professional educational programs, including the professional programs and additional professional programs.